Anticipating the Future of the Ukrainian Political System under the Ukrainian-Russian War - Zeyad Al-Dabbagh; Ghufran Hussein (Tikrit Journal For Political Science, 2023)
The research deals with a set of challenges of the Ukrainian political system in light of its ongoing war with Russia and its repercussions on its future. The research problem began with several questions: What are the causes of the Russian-Ukrainian war? What are the main challenges facing the Ukrainian political system because of the war? What is the future of the Ukrainian political system? The research hypothesis touched on the challenges of the Ukrainian regime, which may take a long time to control and confront them, which will require great efforts to restructure and build Ukrainian society. On the contrary, the political system may collapse and be replaced by another. In order to understand the content of the research, a systematic analysis approach and an inductive approach were used. Important results were reached, including that the geographical location of Ukraine has made it a point of conflict between Russia and the West and that the United States of America and the Ukrainian regime are now facing challenges at all levels. There are a number of future scenarios that are expected to occur, as the Ukrainian regime may succeed in maintaining its existence, or it may fade and end.